Acute effects of antagonist static stretching in the inter-set rest period on repetition performance and muscle activation - Miranda, H.; de Freitas Maia, M.; Andrade Paz, G.; Costa, P. B. (Research in Sports Medicine, 2015)
The purpose of this study was to investigate the effects of antagonist passive static stretching (AS) during the inter-set rest period on repetition performance and muscle activation. Ten trained men (22.4 ± 0.9 years) participated in this study. Two protocols were adopted: Passive recovery (PR) - three sets to repetition failure were performed for the seated row (SR) with two-minute rest interval between sets without pre-exercise stretching; AS - forty seconds of stretching was applied to pectoralis major prior to each set of SR. Significant increases in the number of repetitions were noted under AS compared with PR (p < 0.05). Significant increases on latissimus dorsi (p = 0.002) and biceps brachii (p = 0.001) muscle activity were noted inter-sets under the AS compared with the PR condition. Therefore, the AS adopted during the inter-set rest period may enhance repetition performance and activation of agonist muscles in an acute manner.